Exploring the performance of GaN trench CAVETs from cryogenic to elevated temperatures - Wen, X.; Lee, K.; Kasai, H.; Noshin, M.; Meng, C.; Chowdhury, S. (Frontiers in Electronics, 2025)
Fabricated GaN trench current aperture vertical electron transistors (CAVETs) were characterized across a wide temperature range for the first time, including in situ cryogenic measurements down to 10 K and ex situ thermal shock testing at elevated temperatures of 773 K and 1073 K. The device featured a highly conductive AlGaN/GaN channel regrown on p-GaN following trench etching. As the temperature decreased, the field-effect mobility in the regrown two-dimensional electron gas (2DEG) channel increased from 1886 cm2/(V∙s) at 296 K to 3577 cm2/(V∙s) at 10 K. The device maintained a stable threshold voltage (VTH). The subthreshold slope (SS) decreased from 98.32 mV/dec to 51.31 mV/dec, and the Ion/Ioff ratio increased from 3 × 109 to 9 × 1010 over the same temperature range. The specific on-state resistance (Ron,sp) decreased from 1.02 mΩ cm2 at 296 K to 0.586 mΩ cm2 at 10 K. Furthermore, 1-min thermal shock testing was conducted as a preliminary method to assess the resilience of trench CAVET at elevated temperatures. The device maintained field effect transistor (FET) functionality after exposure to 773 K, albeit with reduced current. Testing at 1073 K resulted in more significant performance degradation, including a sharp increase in Ron,sp and failure to achieve pinch-off due to a pronounced surge in gate leakage.